Information and Communication Technology adoption and its determinants among smallholder maize farmers in Mqanduli, Eastern Cape Province, South Africa - Machethe, Charles Lepepeule (University of Pretoria, 2023)
Thesis (MAgric (Rural Development))--University of Pretoria, 2022.